Kebumen Cares through Free Circumcision at Taman Winangun Kebumen Islamic Boarding School - Sawiji, Sawiji; Nugroho, Irmawan Andri; Santoso, Dadi (Universitas Muhammadiyah Surakarta, 2023)
Circumcision is an obligation for Muslims. declared an obligation because it has been exemplified in the sunnah of the Prophet. It is stated in Siroh Nabawiyah that Rasulullah SAW performed circumcision when he was 7 days old. However, socialisation of the sunnah of Rasulullah Muhammad SAW in Indonesian society is mostly carried out when children are 5 years old or older. Currently, circumcision, or what is more commonly referred to ascircumcision,